Er:YAG Laser: A New Technical Approach to Remove Torus Palatinus and Torus Mandibularis - J. P. Rocca; H. Raybaud; E. Merigo; P. Vescovi; C. Fornaini (Hindawi Limited, 2012)
Objective. The aim of this study was to assess the ability of Er:YAG laser to remove by excision torus mandibularis and to smooth torus palatinus exostosis. Materials and Methods. Torus mandibularis (TM) and torus palatinus (TP) were surgically eliminated via the Er:YAG laser using the following parameters: TM: output power ranging from 500 to 1000 mJ, frequency from 20 to 30 Hz, sapphire tips (diameter 0.8 mm), air-water spray (ratio 5/5), pulse duration 150 μsec, fluence ranging from 99592 J/cm2 to 199044,586 J/cm2. TP: a peeling technique was used to eliminate TP, as excision by slicing being impossible here. Results. TM: excision was obtained after 12730 pulses. TP: smoothing technique took more time compared with excision. Once peeling was considered to be accomplished, the use of a surgical rasp was necessary to eliminate bone spicules that could delay the wound to heal in good conditions. Conclusion. Er:YAG excision (TM) or Er:YAG peeling (TP) are safe clinical techniques easy to practice even if the time required for excision or surface smoothing is more than the time required with bony burs and high speed instruments.